2003
DOI: 10.1002/bjs.4035
|View full text |Cite
|
Sign up to set email alerts
|

Factors and consequences of conversion in laparoscopic sigmoidectomy for diverticular disease

Abstract: Surgical experience and severe diverticular disease are predictive factors for conversion in laparoscopic elective sigmoidectomy. Even if necessary, conversion does not increase the morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 14 publications
6
53
2
6
Order By: Relevance
“…2,3 However colovesical fistulas are still considered a contraindication as a result of previously reported increased operating times and conversion rates. [4][5][6][7] A review of the literature indicated very few studies on the laparoscopic management of diverticular colovesical fistulas exist. 4,8,9 The outcomes of recent studies are difficult to interpret as many have incorporated both recurrent uncomplicated and complicated disease, have not differentiated between colovesical fistulas and other diverticular fistulas, [10][11][12][13][14][15] or have included fistulas of various aetiologies.…”
mentioning
confidence: 99%
“…2,3 However colovesical fistulas are still considered a contraindication as a result of previously reported increased operating times and conversion rates. [4][5][6][7] A review of the literature indicated very few studies on the laparoscopic management of diverticular colovesical fistulas exist. 4,8,9 The outcomes of recent studies are difficult to interpret as many have incorporated both recurrent uncomplicated and complicated disease, have not differentiated between colovesical fistulas and other diverticular fistulas, [10][11][12][13][14][15] or have included fistulas of various aetiologies.…”
mentioning
confidence: 99%
“…In terms of inflammatory cytokine levels, however, the minimal invasiveness of LS remains controversial. Some studies have reported significantly lower inflammatory cytokine levels after LS [15,16] , whereas others have found no significant difference in such levels between LS and OS [17,24,25] . Further studies are needed to objectively evaluate the minimal invasiveness of LS for colorectal cancer.…”
Section: Minimal Invasiveness Of Laparoscopic Colectomymentioning
confidence: 98%
“…Compared with OS, LS offers many benefits, such as a small surgical wound, good esthetic results, less pain, decreased use of analgesics, early recovery of intestinal peristalsis, and a shorter hospital stay [14][15][16][17][18][19][20][21][22][23] . In terms of inflammatory cytokine levels, however, the minimal invasiveness of LS remains controversial.…”
Section: Minimal Invasiveness Of Laparoscopic Colectomymentioning
confidence: 99%
“…In terms of inflammatory cytokine levels, however, the minimal invasiveness of laparoscopic surgery remains controversial. Some studies have reported significantly lower inflammatory cytokine levels after laparoscopic surgery 12,20) , whereas others have found no significant differences in such levels between laparoscopic surgery and open surgery 13,21,22) . Further studies are warranted to objectively evaluate the minimal invasiveness of laparoscopic surgery for colorectal cancer.…”
Section: Colon Cancermentioning
confidence: 99%
“…Compared with open surgery, laparoscopic surgery offers many benefits, such as smaller surgical wounds, good esthetic results, less pain, decreased use of analgesics, early recovery of intestinal peristalsis, and a shorter hospital stay [10][11][12][13][14][15][16][17][18][19] . In terms of inflammatory cytokine levels, however, the minimal invasiveness of laparoscopic surgery remains controversial.…”
Section: Colon Cancermentioning
confidence: 99%